Addressing failed water infrastructure delivery through increased accountability and end-user agency: the case of the Sekhukhune District, South Africa - Hofstetter, Moritz; Bolding, A.; van Koppen, Barbara (2020)
Despite progressive policies and a legal framework that includes the constitutional right to sufficient water, there are still enormous problems with water service delivery in low income rural South Africa. To understand the factors responsible for the observed discrepancy between ambitious policies and disappointing water service delivery, we undertook an analysis of the implementation of these policies in Sekhukhune District, South Africa; we scrutinised the public service water delivery in that district using an actor-oriented approach. We found that during the four phases of public water services delivery – identification, planning, construction and operation – practices often deviated from the stipulated policies; we also found that accountability relations between service delivery agencies and end users were undermined by gatekeeping and patronage. We argue that there is no need for major policy changes; we concluded from our research that by mobilising mechanisms that are based on existing policies, accountability relations can be strengthened and service delivery improved. We describe an experimental approach which focuses on budget transparency and end-user-driven development; it is an approach which aims at strengthening the agency of end users while limiting possibilities for rent-seeking and gatekeeping by councillors and contractors.